2014
DOI: 10.1007/s00253-014-6227-0
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of yellow Monascus pigments by extractive fermentation in nonionic surfactant micelle aqueous solution

Abstract: Monascus species can produce various secondary metabolites of polyketide structure. In the current study, it is found that an interesting phenomenon, i.e., submerged culture of Monascus species in an aqueous solution majorly accumulated intracellular orange Monascus pigments exhibiting one peak at 470 nm with absorbance of 32 OD while extractive fermentation in a nonionic surfactant micelle aqueous solution produced extracellular and intracellular yellow Monascus pigments exhibiting one peak at 410 nm with abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 34 publications
2
28
1
Order By: Relevance
“…In our previous work, extractive fermentation in a nonionic surfactant micelle aqueous solution had exported intracellular Monascus pigments into its extracellular broth, in which high fraction of yellow Monascus pigments was accumulated in the extracellular broth (nonionic surfactant micelle aqueous solution) [16]. The production of a large amount of yellow Monascus pigments by extractive fermentation provides a chance for preparation of yellow Monascus pigments.…”
Section: Introductionmentioning
confidence: 98%
“…In our previous work, extractive fermentation in a nonionic surfactant micelle aqueous solution had exported intracellular Monascus pigments into its extracellular broth, in which high fraction of yellow Monascus pigments was accumulated in the extracellular broth (nonionic surfactant micelle aqueous solution) [16]. The production of a large amount of yellow Monascus pigments by extractive fermentation provides a chance for preparation of yellow Monascus pigments.…”
Section: Introductionmentioning
confidence: 98%
“…Micelle aqueous solution, from addition of nonionic surfactant (Triton X-100) into the fermentation broth, facilitates intracellular conversion of MOPs to MYPs. MYPs are simultaneously extracted from the mycelia and effectively secreted into the broth (Kang et al 2013;Xiong et al 2015). These new techniques require more investigation and development before application at commercial scales.…”
Section: New Methods In Fermentationmentioning
confidence: 99%
“…This result revealed that the MpigE gene plays an irreplaceable role in converting biosynthesized MYPs into MOPs. Lately, conversion between MYPs and MOPs has been reported in an extractive Monascus fermentation using a nonionic surfactant micelle, aqueous solution with Triton X-100 (Xiong et al 2015). According to these reports, Fig.…”
Section: Biosynthetic Pathways Of Mypsmentioning
confidence: 95%
See 1 more Smart Citation
“…Extracellular pigment is extracted from media because it is spread outside the cells (Xiong et al 2015;Akilandeswari & Pradeep 2016). Pigment production depends on several conditions, such as nutrient in media, light intensity, pH, trace elements, temperature and agitation (Mugesh et al 2014;Bühler et al 2015;Patil et al 2015;Shi et al 2015).…”
Section: Antibacterial Activity Of Red Pigment Produced From Fungus Rmentioning
confidence: 99%